The diagnosis and follow-up of patients with penile fracture - Kanbay, Mustafa; Özdemir, Enver; Ardiço?lu, Aslan; Yalçin, Orhan; Atikeler, Mustafa Kemal; Yüzgeç, Veysel (My University, 2003)
Introduction: Penile fracture or traumatic rupture of the corpora cavernosa is quite rare and usually develops as a result of direct penile trauma, usually during the sexual intercourse. Erection causes thinning and stretching of tunica albuginea, and bending force may result in a transverse tear of the corpus cavernosum. Optimal diagnostic and treatment procedures have not been yet established. Herewith, we purposed to present the characteristics of our patients with penile fracture that treated at urology department of Firat Medical Centre. Materials and Methods: From may 1999 to November 2002 seven patients with penile trauma between the ages of 19 to 42 years (median±SD, 36±9.44) were operated at Firat Medical Center. The diagnoses were established with history (pain, typical fracture sound, swelling with penile deformity) and physical examination. The duration from trauma to the operation procedure ranged from 2 to 20 hours (median±SD, 7±6.87). Retrograde urethrography was performed because of urethroragia during physical examination. In all of the patients to prevent from urethral laseration during the operation, a 16F double lumen urethral Folley catheter was inserted. Following surgical exploration by a subcoronal incision, the hematoma was discarded and fracture area was sutured. Results: A sudden pain in the penis, edema, color change, sudden detumescence was the main patient complaints. In a patient with urethroragia, urethrography demonstrated extravasation, and the diagnosis of incomplete urethral rupture was established. Physical examination and history were adequate for diagnosis for all the remaining six patients (85.7%). There was urethral laseration in one patient and deep dorsal venous rupture in another patient. The corporeal rupture in the other five patients was repaired. The rupture in the tunica albuginea was ranged from 5 to 20 mm (median 9 mm). The duration of hospitalization was ranged from 2 to 4 days (median 3 days). As for complications, minimal penile curvature in one patient, discomfort during sexual intercourse in another patient and wound infection in one patient were observed. No additional therapy was required for the complications. Conclusions: Penile fracture is an urgent urologic pathology. After completion of history and physical examinations, reparative operation should follow rapidly. Delayed interventions increase discomfort during sexual intercourse due to fibroid changes in the corporal bodies. Vascular rupture associated with penile fracture is rare, but may be seen as in our study. Erectile dysfunction, an important complication of penile fracture, was not observed during the 24-month follow-up period of our patients. History and physical examination are mostly adequate for definitive diagnosis and rapid initiation of therapy. Cavernosography is not required routinely. In case of urethroragia at the time of examination, a retrograde urethrography should be performed.
Pe?il Fraktürlü Olgularda Tani ve Takip
Keywords: Fracture; Injury; Penis; Trauma